Casos de encefalites virais e Síndrome de Guillain Barré em pacientes internados no HUJBB no período de 2000 / 2005: possível confusão diagnóstica com raiva paralítica transmitida por morcegos - BORGES, Juliana de Araújo (2022)
Between the months of March and May of 2004, had occurred in the state of Pará, in the cities of Portel and Viseu, 21 cases of human rabies transmitted by bats. The clinical findings of the illness were characterized by the paralytic form, without suggestive signals and symptoms of the classic rabies, such as deliriums, hallucinations, hydrophobia and aerophobia. Animal rabies transmitted by bats, especially in bovines, comes occurring in the last two years in diverse localities of the State of Pará. As other human illnesses of similar clinical presentation they are frequent causes of internment in the School Hospital João of Barros Barreto, it was questioned occurrence of human rabies in its paralytic form has more time in the state that have been confused with other diseases of the central and peripheral nervous system. The objective of the work aimed at to characterize the cases of human rabies transmitted by bats that had been interned in the School Hospital João of Barros Barreto in 2004, comparing the results gotten with those findings between the patients with Guillain Barré Syndrome and encephalitis interned in the same hospital in the last five years, in the attempt to identify to possible cases of human rabies in its paralytic form that have been diagnosised as another illness of similar clinical findings. Nine cases of paralytic form of rabies disease had been described, eight originating of Portel and one of Viseu, all occurrences in 2004, in which predominated persistent fever, paresthesia and ascendent anti-symmetrical paralysis of inferior members, urinary retention and intestinal constipation. The most important findings in exams had been leukocytosis with neutrophily, beyond pleocytosis of low moderate. Of the four cases of Guillain Barré Syndrome, three could be fit as suspected of rabies, either for the short time of illness, either for the clinic with fever, disorientation and until sialorrea. In the 23 cases of encephalitis / meningoencephalitis studied, several framed as bacterial or purulent meningoencephalitis, the bacterial etiology remained questioned, without disgnostic clarification. Eight patients had only presented drawn out time of illness (more than three weeks), without ventilatory support, what it speaks against rabies diagnosis, illness of faster evolution, of one two weeks. Two patients had history of aggression for animal few weeks before the illness. Thus, at least 15 patients, with clinic of encephalitis / meningoencephalitis, presence of fever, disorientation, urinary retention, some with intestinal constipation and until sialorrea, among others also frequent signals and symptoms in rabies disease, must have the diagnosis of encephalitis for the questioned rabies virus, with diagnostic inquiry for the same one. This work suggests that the occurrence of human rabies can more be raised of what the notified one until then, being important the monitoring of Guillain Barré Syndrome and encephalitis /meningoencephalitis cases of fatal evolution, in days or few weeks, without clarified cause.